Development of Heyzine Flipbook-Based E-Module Integrated with PhET, Kahoot, and Padlet to Support Students’ Scientific Literacy - Vitaya, Sisca; Halim, Abdul; Yusrizal, Yusrizal; Evendi, Evendi; Huda, Ismul (Jurnal Pendidikan Progresif, 2025)
Development of Heyzine Flipbook-Based E-Modul Integrated with PhET, Kahoot, and Padlet to Support Students’ Scientific Literacy. Objectives: This study aims to develop an interactive e-module based on the Heyzine Flipbook platform, integrated with PhET simulations, Kahoot quizzes, and Padlet reflections. The module is designed to support students’ scientific literacy, particularly on the topic of work and energy. The urgency of this research stems from the low scientific literacy performance of Indonesian students in the 2022 PISA assessment, which indicated that most students remain below the basic proficiency level in understanding science. Methods: This study used a Research and Development (R&D) approach with the ADDIE model, involving 32 students at SMA Negeri 1 Lhokseumawe. A one-group pretest-posttest design was applied. Data were obtained from expert validation sheets, essay-based tests, and student questionnaires. Validity and reliability were measured using Aiken’s V and inter-rater agreement. Practicality was analyzed through student feedback using quartiles. N-gain analysis was used to determine posttest improvement after using the e-module. Findings: The developed e-module was classified as highly feasible based on expert validation, with Aiken’s V scores of 0.915 for the media aspect and 0.900 for the content aspect, and inter-rater agreement values of 0.774 (media) and 0.765 (content). In terms of practicality, the e-module received very positive responses from students, with a score of 90.07%. Furthermore, the N-gain analysis yielded a score of 0.753, which falls into the high category, indicating that the e-module contributed to improving students’ scientific literacy. Conclusion: These results indicate that the developed Heyzine Flipbook-based e-module is feasible, practical, and has the potential to support the enhancement of students’ scientific literacy in 21st-century physics education. Keywords: heyzine flipbook, e-module, science literacy, PhET simulation, kahoot, padlet.